A quantitative Inquiry into the Keywords between Primary and Reference Arabic Corpora. Issue 2 (3rd April 2018) - Al-Thubaity, Abdulmohsen; Almujaiwel, Sultan
Abstract: This study primarily addresses the influence of a reference corpus in terms of its size, topics, time, and geographical area on keyword extraction. It sets out the underlying principles of the key statistical measures, and shows the influence of key statistical measures on keywords and the similarities and differences between such measures. The study provides simple insight into the words that can be easily excluded, with a core focus on the type of study used, and the number of keywords selected for further consideration. We have explored the influences indicated above using an empirical method, with an emphasis on the quantitative measures of the keywords in question. These statistical measures are found to influence the results of the keywords differently. We have also conducted an analysis of keywords retrieved during experiments, taking into consideration keywords' complexity and associations. The results show the major influence of the reference corpus is related to its topics, whereas size, time, and geographical area are less influential.